Emerging outsource agricultural services enable farmer adaptation in agrifood value chains: A product cycle perspective - Reardon, Thomas; Awokuse, Titus; Belton, Ben; Liverpool-Tasie, Lenis Saweda O.; Minten, Bart; Nguyen, Genevieve; Qanti, Sara; Swinnen, Johan; Vos, Rob; Zilberman, David (Elsevier, 2024)
Outsource agricultural service enterprises emerged a century ago in high-income countries and in the past several decades in developing regions. We contribute by analyzing and illustrating the emergence of these services from the perspective of phases of the Product Cycle. These services help farmers adapt to international and domestic agrifood value chains: (1) in the commoditization phase, e.g., with rice combine harvesting services in China and Myanmar for domestic and export markets; (2) in the early product differentiation phase into quality traits, e.g., with horticultural services to Ethiopian and Indonesian farmers for urban wholesale markets; (3) in the advanced product differentiation phase into environmental traits, e.g., with A-Z services to help French farmers grow eco-labeled vegetables for supermarkets. These services addressed farmers’ shortfalls in information, skills, labor, and equipment. The services are supplied by medium/large farmers with excess capacity say of a combine; by wholesalers who want to reduce search costs and risks; by input “agro-dealers”; and by agribusinesses servicing their outgrowers. In new cases shown in France, outsource firms partner with farm input companies such as Bayer or with robot/drone companies. Governments have – and can do much more to – support the emergence of these services such as in developing regions today through: (1) promotion of a business ecosystem, based on policies of investment in hard and soft infrastructure, favoring the coadaptation of these firms with farmers’ needs; (2) policies facilitating access, such as through import liberalization, of equipment and seeds and chemicals.